2008
DOI: 10.1108/03684920810851177
|View full text |Cite
|
Sign up to set email alerts
|

The cybernetics of social change – and history

Abstract: PurposeThis paper aims to show how basic cybernetics principles of the interaction of two or more goal‐oriented systems determine the possibilities of social change – and of history.Design/methodology/approachThe starting‐point is the assumption of a social unit organized in two levels in which leaders and subordinated members share mutual goal‐values. As sources for differentiation within this unit diverging individual strivings and questions of leadership (i.e. defining goals, internal and external policy) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In a previous paper we have shown that the minimal content of an elementary decision can be derived from a simple feedback system (Nechansky, 2006). Applying that approach to decision making on a macro level we showed that the possibilities for interactions between goalorientated systems are limited (Nechansky, 2007), which explains the limited behavioural and developmental options even of social systems (Nechansky, 2008a(Nechansky, , 2008b.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper we have shown that the minimal content of an elementary decision can be derived from a simple feedback system (Nechansky, 2006). Applying that approach to decision making on a macro level we showed that the possibilities for interactions between goalorientated systems are limited (Nechansky, 2007), which explains the limited behavioural and developmental options even of social systems (Nechansky, 2008a(Nechansky, , 2008b.…”
Section: Introductionmentioning
confidence: 99%
“…In “Elements of a cybernetic epistemology”, Nechansky (2007, 2008a, 2008b) shows that four modes of coexistence result as a cybernetic necessity that arise from only four factors (Nechansky, 2008a, p. 85): the number of systems trying to control one controlled system; the relative positions of their goal-values in relation to each other; the relative positions of their goal-values in relation to the actual state of the controlled system; and the variety and power of their actions.” …”
Section: A Brief Comparison With Nechansky’s Theorymentioning
confidence: 99%
“…Nechansky (2008b), in his article on “The cybernetics of social change – and history” when considering the context of foreign policy, refers to “submissive foreign policy”: “Occasionally we find that a social unit surrenders to a too strong opponent, or decides to merge with another one to get protection against such an opponent. The resulting mode of coexistence is the lower position in a hierarchy”.…”
Section: A Brief Comparison With Nechansky’s Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…It can serve as a first approximation for any decision‐making process. Making the formula for an elementary decision and the goal orientation of decisions explicit, makes it easy to apply cybernetics, and aspects of control theory, to social systems (Nechansky, 2007, 2008a, c).…”
Section: Feedback Systemsmentioning
confidence: 99%